2014
DOI: 10.1007/s40258-014-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar Granulocyte Colony-Stimulating Factor Uptakes in the EU-5 Markets: A Descriptive Analysis

Abstract: The competition with G-CSF biosimilars varies significantly between EU-5 countries, probably because of G-CSF distribution channel differences. Currently, this competition is not mainly based on prices, but on local political options to stimulate tendering between them and recently branded second- or third-generation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…One study estimated the impact of biosimilar entry in terms of healthcare systems savings between 2007 and 2020 for eight EU countries (France, Germany, Italy, Poland, Romania, Spain, Sweden, and the UK), ranging from €11.8 billion to €33.4 billion [12]. Other qualitative studies assessed the levers and barriers to the uptake of biosimilars based on analysis of biosimilar uptake, price reduction, and various policies implemented across EU MS [2,8,[13][14][15][16][17] One quantitative study (Rovira et al [18]) assessed market dynamics of biosimilars in 24 EU MS, as well as Norway and Switzerland, between 2007 and 2010 using bivariate regression, and reported faster launch of biosimilars after marketing authorisation, associated to countries' gross national income and expenditure on health, pharmacists' generics substitution (inversely), and medicines' price level index. A recent survey providing an overview of pricing and reimbursement policy approaches across Europe for biological medicines, and specifically applied to biosimilars showed heterogeneity in policies and their implementation between the different countries [11].…”
Section: Background and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…One study estimated the impact of biosimilar entry in terms of healthcare systems savings between 2007 and 2020 for eight EU countries (France, Germany, Italy, Poland, Romania, Spain, Sweden, and the UK), ranging from €11.8 billion to €33.4 billion [12]. Other qualitative studies assessed the levers and barriers to the uptake of biosimilars based on analysis of biosimilar uptake, price reduction, and various policies implemented across EU MS [2,8,[13][14][15][16][17] One quantitative study (Rovira et al [18]) assessed market dynamics of biosimilars in 24 EU MS, as well as Norway and Switzerland, between 2007 and 2010 using bivariate regression, and reported faster launch of biosimilars after marketing authorisation, associated to countries' gross national income and expenditure on health, pharmacists' generics substitution (inversely), and medicines' price level index. A recent survey providing an overview of pricing and reimbursement policy approaches across Europe for biological medicines, and specifically applied to biosimilars showed heterogeneity in policies and their implementation between the different countries [11].…”
Section: Background and Objectivementioning
confidence: 99%
“…Several factors have been reported as potential drivers of biosimilar uptake and might explain the differences observed between EU MS, i.e., physician and patient adoption of biosimilars, national healthcare systems specificities in terms of pricing, reimbursement, and procurement policies [4,19] Bocquet et al [16,20] reported that price difference between originator and biosimilar was not a main driver of EPO and G-CSF uptake; a low biosimilar uptake was partly explained by price cut of originators prior to biosimilar entry, as well as the development of new generation products competing with biosimilars. A recent study has shown a weak correlation between biosimilar uptake and price reduction [21].…”
Section: Background and Objectivementioning
confidence: 99%
“…Internal reference pricing [19][20][21][22][23][24] IRP is in place for biosimilars in five (France, Germany, Hungary, Poland, and Spain) out of the 10 selected countries, at the fourth Anatomical Therapeutic Chemical (ATC) classification level (therapeutic/pharmacological/ chemical subgroup) and/or at the fifth level (chemical substance) [25]. In Hungary, there is also a policy called 'preferred reference pricing system', applicable when more than two versions of a biologic medicine are available; this policy sets preferred price ranges based on the reference price for reimbursement, i.e.…”
Section: Supply-side Policies For Biosimilarsmentioning
confidence: 99%
“…In order to describe the dynamics at work on the biosimilar market and to determine the biosimilar capacity to compete with other biologics-and after having previously analyzed the G-CSF market 8 -the EPO market was a natural analysis to make in retrospect 9,10 . The EPO class is that which generates more expenses around the world (7.6 billion dollars in 2012), where the highest number of biosimilars can be found, for which the number of laboratories is the most important and for which we have the highest number of biosimilar-using experiences.…”
mentioning
confidence: 99%
“…In Germany, the heterogeneously implemented incentives promoting the use of biosimilars seem to significantly increase the EPO-BIOSIM uptake. Their impact nonetheless has to be put into perspective, as biosimilar G-CSF uptakes in Germany remain weak in relation to other European countries, which have not implemented equivalent incentives 8 . Moreover, the non-coercive aspect of implemented quotas cannot guarantee their real efficiency, and other studies show that biosimilar uptake rates can easily vary from one German region to another 11 .…”
mentioning
confidence: 99%